Hepatocyte lesions and cellular immune response in yellow fever infection - Quaresma, Juarez A. S.; Barros, Vera L. R. S.; Pagliari, Carla; Fernandes, Elaine R.; Andrade, Heitor F.; Vasconcelos, Pedro F. C.; Duarte, Maria I. S. (Elsevier B.V., 2007)
The study of the in-situ cellular immune response is very important for the understanding of different liver infections. In the present study, 53 liver samples obtained by viscerotomy from patients who died during the course of jungle yellow fever were analyzed. The diagnosis was confirmed by serology, viral isolation and virus-specific immunohistochemistry. The specimens were analyzed by immunohistochemistry using specific antibodies for apoptosis, CD45RO, CD4, CD8, CD20, S100, CD57 and CD68. Quantitative analysis of the labeling pattern showed a clear predominance of the different phenotypes in the portal tract and midzone region of the acini. There was a predominance of T CD4+ lymphocytes, accompanied by the presence of T CD8+ lymphocytes, natural killer cells (CD57), macrophages and antigen-presenting cells (S100). The disproportion between the intensity of inflammation and the degree of hepatic injury was probably due to the intense apoptotic component, which classically does not induce an inflammatory response. The present study demonstrates that, despite the disproportion between injury and inflammation, the cellular immune response plays an important role in the pathogenesis of the hepatocytic injury observed in yellow fever, probably as a result of cytolytic actions through mechanisms involving MHC II and the activation of Fas receptors and granzymes/perforins. (C) 2006 Royal Society of Tropical Medicine and Hygiene. Published by Elsevier Ltd. All rights reserved.
Keywords: yellow fever; arbovirus; Flavivirus; immunologic; markers; apoptosis; Brazil